2021
DOI: 10.1111/jcmm.16747
|View full text |Cite
|
Sign up to set email alerts
|

Kakonein restores diabetes‐induced endothelial junction dysfunction via promoting autophagy‐mediated NLRP3 inflammasome degradation

Abstract: In diabetes‐induced complications, inflammatory‐mediated endothelial dysfunction is the core of disease progression. Evidence shows that kakonein, an isoflavone common in Pueraria, can effectively treat diabetes and its complications. Therefore, we explored whether kakonein protects cardiovascular endothelial function by inhibiting inflammatory responses. In this study, C57BL/6J mice were injected with streptozocin to establish a diabetes model and treated with kakonein or metformin for 7 days. The protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Additionally, there is evidence to indicate that hyperglycemic conditions cause endothelial cell dysfunction and NLRP3 inflammasome activation ( 75 ). MCC950, an NLRP3 inhibitor ( 11 ), tetramethylpyrazine ( 76 ), hydrogen sulfide ( 77 ) and Kakonein ( 78 ) have been shown to improve endothelial dysfunction by suppressing NLRP3 inflammasome activation or the production of its effectors, caspase-1 and IL-1β. Moreover, MCC950 targets NLRP3-mediated inflammation, and reduces plaque development, promotes plaque stability and improves diabetes-associated vascular disease ( 79 ).…”
Section: Pathophysiological Role Of the Nlrp3 Inflammasome In Inflamm...mentioning
confidence: 99%
“…Additionally, there is evidence to indicate that hyperglycemic conditions cause endothelial cell dysfunction and NLRP3 inflammasome activation ( 75 ). MCC950, an NLRP3 inhibitor ( 11 ), tetramethylpyrazine ( 76 ), hydrogen sulfide ( 77 ) and Kakonein ( 78 ) have been shown to improve endothelial dysfunction by suppressing NLRP3 inflammasome activation or the production of its effectors, caspase-1 and IL-1β. Moreover, MCC950 targets NLRP3-mediated inflammation, and reduces plaque development, promotes plaque stability and improves diabetes-associated vascular disease ( 79 ).…”
Section: Pathophysiological Role Of the Nlrp3 Inflammasome In Inflamm...mentioning
confidence: 99%
“…In addition, lysosomal damage mediates the activation of the inflammasome-NLR family pyrin domain containing 3 (NLRP3) and the release of high mobility cassette protein 1, leading to endothelial hyperpermeability. However, activating autophagy via the AMPK pathway can inhibit the assembly and activation of NLRP3, restore endothelial connectivity, and reduce endothelial permeability (97,98). Finally, Weikel KA et al found an increase in glycogen synthase kinase 3b (GSK3b) activity in DM patients and animals participating in autophagy inhibition.…”
Section: Ampk Pathwaymentioning
confidence: 99%
“…Autophagy is deemed to be an efficient regulator of NLRP3 inflammasome activation in hyperglycemia-related vascular complications. Puerarin regulates NLRP3 inflammation through autophagy and has protective effects on chronic vascular diseases induced by hyperglycemia [ 102 ]. Inflammation-mediated endothelial dysfunction takes a pivotal effect in cardiovascular disease caused by diabetes.…”
Section: The Role Of Puerarin In Inflammatory Diseasesmentioning
confidence: 99%